EFEKTIVITAS PEMBELAJARAN KOOPERATIF STAD DALAM MENINGKATKAN PERILAKU KETERIKATAN SISWA SD DALAM PELAJARAN MATEMATIKA - Amarilys Andaritidya (Jurnal Psikologi, 2014)
The purpose of the study is to explore the effectiveness of STAD cooperative learning on improving behavior engagement in  mathematics subjects of  fifth grade elementary students. Independent variables in this study is STAD cooperative learning, meanwhile behavior engagement in mathematics subjects as the dependent variables. In this study self efficacy in mathematics also as a covariable. Participant of this study were 60 students in elementary school measured. It has two group, first, 35 students from SD KG I were the experimental group who received STAD cooperative learning, and second, 25 students from SD KG V were the control group who received traditional learning. The method used by this study is quasi experiment with untreated control group design with pretest and posttest, and the data analyzed with Anava mixed design. The result of this study shows that STAD cooperative learning fail to improve behavior engagement in mathematics subjects elementary students.     Keyword: Behavior engagement, STAD cooperative learning, Mathematics subjects